A Pandemic Snapshot: Libraries' Digital Shifts and Disparities to Overcome. Issue 3 (4th May 2023) - Guernsey, Lisa; Prescott, Sabia; Park, Claire
ABSTRACT: In the fall and winter of 2020, New America embarked on a snapshot study to gather data on how – or if – people were discovering, accessing, and using their public libraries during the COVID-19 pandemic, with a focus on materials that libraries made available online. A full report on our findings, titled Public Libraries and the Pandemic: Digital Shifts and Disparities to Overcome, was published in March 2021. This article draws heavily from that report and also includes a policy update related to passage of the Infrastructure Investment and Jobs Act in the Fall of 2021. Analyzing data from a national survey in Fall 2020 of 2, 620 people, we found mixed awareness of the public library's online resources, a shift toward online resources, mostly positive attitudes toward the public library and its online resources, and disparities in access to and use of the public library's online resources. This article also describes one library's creation of a digital navigator program to support digital literacy as an example of how to overcome some of these disparities. We conclude with specific recommendations for improving inclusivity, helping community members gain affordable internet access at home so they can use their library's online materials, and building awareness of library offerings via local organizations and schools. The aim is to leverage the lessons of the pandemic to help libraries launch more equitable ecosystems of learning across communities, providing access to knowledge, resources, and training, online and off.